High and Fast Response of a Graphene–Silicon Photodetector Coupled with 2D Fractal Platinum Nanoparticles. Issue 1 (1st December 2017) - Huang, Kun; Yan, Yucong; Li, Ke; Khan, Afzal; Zhang, Hui; Pi, Xiaodong; Yu, Xuegong; Yang, Deren
Abstract: 2D material‐based electronic devices like graphene–silicon photodetectors (Gr–Si PDs) have attracted much attention of researchers in the past few years. Due to the nature of Schottky junction, Gr–Si PDs have ultrafast response. However, responsivity of Gr–Si PDs is very low, which hinders their practical application. Low work function of Gr and poor absorbance of Si are mainly responsible for this problem. Here, a novel approach for coupling of Gr–Si PDs with 2D fractal platinum nanoparticles (Pt NPs) is demonstrated to enhance the responsivity and speed up the response of Gr–Si PDs at the same time. 2D morphology of fractal Pt NPs helps to overcome the coffee‐ring effect. Fully covered fractal Pt NPs remarkably improve the absorption of Gr–Si PDs by plasmonic effect. Responsivity of Gr–Si PDs thus is remarkably enhanced to 26 A W −1 . Meanwhile, work function of Gr is improved by the physical doping of high‐work‐function Pt NPs. Therefore, the Schottky barrier of Gr–Si junction is increased, resulting in faster response. Improvement in the built‐in electric field reduces the background noise of Gr–Si PDs as well. These results indicate toward a simple and novel approach for fabricating high and fast response Gr–Si PDs. Abstract : A novel approach to enhance the responsivity and the response speed of graphene–silicon photodetectors is demonstrated with 2D fractal platinum nanoparticles. Fully covered platinum nanoparticles improve the responsivity of photodetectors to 26 A W −1, which outperforms similar photodetectors reported so far.